Tecnologias Analítica e de Produção Vegetal de Erythrina velutina Willd. - Oliveira, Polyanna Bárbara de Medeiros (2018)
The species Erythrina velutina Willd., Also known in the Semiarid of Brazil, as mulungu, is a tree of great resistance to drought, providing rusticity and rapid growth, widely used in the recovery of degraded areas, with great distribution in the region. It has chemical and pharmacological characteristics for the production of herbal medicines. The objective of the research is to improve thermoanalytical techniques of vegetal production of the species ErythrinavelutinaWilld. as a way of maximizing the knowledge of the pharmacological potentiation of the vegetal raw material in the Brazilian semi-arid region. Five matrices of E. velutina were selected, in the region of CaririOcidental in the municipality of Serra Branca, located in Paraíba, Brazil. Sorts of the collected material were made and morphological analyzes of the seeds were carried out. Starting with biometrics, 100 seeds of each matrix were selected, where the parameters of length, width and fresh mass of each seed were verified. In the biological characterization, emergency analyzes were performed in order to obtain better results with pre-germination treatments. For the implementation of plant production, 96 seeds of each matrix were sown in buckets, observing the emergence of seedlings, in order to characterize them from emergence, development and withdrawal, in pre-defined periods. The physico-chemical analyzes were organized in conventional analyzes, humidity and ashes, as well as in thermoanalytical analyzes, TG and DTA, in differentiated granulometry, in order to evaluate kinetic parameters and thermal parameters. For the biometric results of the seeds we obtained averages of the parameters of length, diameter and mass for each matrix. In plant production, analyzing the emergence data of the seedlings, there was a significant difference between the matrices, varying between 70.8% and 34.4%. Thus, matrix 2 and matrix 4 presented the same emergency index, 70.8%. In terms of mortality, seedlings obtained low mortality rates, only in matrix 1 (2.1%) and matrix 2 (10.4%), these indices were recorded. In the measurements of seedlings at 30, 60, 90 and 120 days, mean values of length between 38.09 cm and 57.8 cm and stem diameter between 16.13 mm and 19.39 mm were obtained. The seeds presented a singularity in the moisture content among the matrices of the species, presenting a percentage loss of moisture between 4.27% and 5.24%. Likewise, it was used to determine the ash content, with a percentage value between 26.7% and 43.2%. The DTA curves by GT showed three exothermic events with a mean temperature of 467.61 ° C. The TG curves showed five mass degradation events in the inert and oxidative atmosphere, where the main degradation step was observed in the third event, presenting respective temperature and mass loss ranging from 213.26 - 378.46 ° C and 34.14- 40,17% inerte, e 252,87 - 466,98ºC e 20,28 - 22,73% oxidativa, para todos as razões. eumaentalpia com média de 535,79 kJ / g. On the other hand, the DTA by GP curves showed variations in the number of peaks, showing two or three events with exothermic characteristics. Thus, it can be concluded that matrix 3 showed a higher number of germinated seeds, consequently, presented the highest growth measures in 30 and 120 days. In the withdrawal of some seedlings the largest fresh mass occurred for the matrix 3. In the Differential Thermal Analysis (DTA) the matrix 3 presented a larger enthalpy.